Evaluation the Levels of Serum Hormones (Progesterone, Estradiol, and hCG) in Preeclamptic IraqiPregnancies (Baghdad Science Journal, 2012)
This study aimed to evaluate serum levels of steroid hormones and human chorionic gonadotropin (hCG) hormone in preeclamptic Iraqi pregnancies compared to those of healthy pregnancies.This study enrolled 120 pregnant women, divided into four groups:1. 30 healthy pregnant women.2. 37 pregnant women with mild preeclampsia3. 53 pregnant women with severe preeclampsia4. 90 pregnant women with preeclampsia Preeclamptic women and their severe cases but not mild cases had significantly (P